Synthesis of Pyridyloxycyclophosphazene and its Cu(I) Complex - Boncukcu, Elvin; Elmali, Fikriye Tuncel; Demirhan, Nebahat (IOS PRESS, 2013)
A new pyridyloxycyclophosphazene, called 2,2'-bis[2-oxy-6-methyl- pyridine]-4,4,6,6-bis[spiro(2',2 ''-dioxy-1,1'-biphenyl)]cyclotriphosphazane (BB-CP) has been synthesized from the reaction of 2,2-dichloro-4,4,6,6-bis[spiro(2',2 ''-dioxybiphenyl)] cyclotriphosphazane (2Cl-CP) and 2-hydroxy-6-methylpyridine (HMP). The Cu(I) complex of this ligand has been prepared. The new ligand and Cu(I) complex were characterized by FT-IR, (1) H NMR, P-31 NMR, UV-vis, mass spectra, elemental and thermal analyses.
Keywords: Pyridine; cyclophosphazane; Cu (I) complex; 1,10-PHENANTHROLINE; POLYPHOSPHAZENES; Chemistry